Samle, telle, regne, fortolke - tilbakeblikk på Kreftregisterets statistikkproduksjon og forskning gjennom 70 år - Tom K. Grimsrud (Norsk Forening for Epidemiologi, 2022)
The Cancer Registry of Norway was established 1952 with important initiatives and impetus from WHO and The Norwegian Cancer Society. The main purpose of the Registry has been to describe and explain trends and frequencies in cancer incidence, to analyse the need for cancer prevention and therapy, inclusive of aetiological research, and to study the effects of cancer control. The first report on cancer incidence covering 1953-1954 was published in 1959. In the 1950s, stomach cancer was the most common cancer among men and women combined, breast cancer was the most frequent cancer in women, and lung cancer was rising in men (observed in the mortality rates). Identification and the full understanding of different aspects of smoking and cancer remained a challenge from the 1950s through the 1980s, nationally and internationally. From 1977 to 1989, the Cancer Registry produced incidence reports every year with tables presenting absolute numbers and crude rates. In the 1990s, age-standardisation appeared in routine data, both in national, county, and historical rates. During the initial decades, important scientific support was received from Denmark, UK and the USA. Nordic co-operation has always been vital for exchange of experience, for comparisons, and for addressing rare cancer forms. Studies of occupational cancer emerged from the early 1970s, starting with nickel refiners and asbestos cement workers. The number of scientific publications and defended doctoral theses rose markedly during the 1990s and after, with projects directed towards aetiology (lifestyle, medication, occupation, environmental exposures), early diagnosis and screening, clinical issues, predictions, survival, biomarkers, and socio-economic factors.